θ-Theory and Configuration - Kawai, Michiya (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 2002)
AbstractChomsky 1993, 1995, 2000, 2001a, 2001b, following Hale and Keyser 1993, assumes that θ-roles are assigned in a certain structural configuration at logical form (LF), to be referred to as the configurational theory of θ-role licensing (CTTL). This approach eliminates the relevance of argument (θ-) structure within narrow syntax (NS), thus rendering D-structure superfluous. This study examines how argument (θ-) structure and other base properties (traditionally associated with D-structure) are captured, without D-structure, in minimalism. While Chomsky advocates the CTTL, θ-theory appears to covertly play a crucial role in NS: the properties associated with D-structure are not fully subsumed under LF. Hence, the base properties cannot be fully assumed by the conceptual-intentional interface.